Industrial training report: Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) / Fatin Nadzirah Maarof - Maarof, Fatin Nadzirah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
This report describes the experiences gained during a six-month internship at Perbadanan Perpustakaan Awam Melaka (PERPUSTAM) from 19 February 2024 to 4 August 2024. As a Library Management student at Universiti Teknologi MARA (UiTM), completing an internship is a requirement in the 7th semester. This practical experience helps assist between what I've learned in class and how libraries function. The report is divided into four chapters. Chapter 1 introduces the background of PERPUSTAM. Chapter 2 explains how different departments work together within PERPUSTAM. Chapter 3 details my tasks during the internship, such as organizing library activities, managing digital resources, and even cataloging materials. Finally, Chapter 4 reflects on my overall experience, including how I applied theoretical knowledge in a real library setting and the valuable lessons I learned.